Studies of shorebirds at Lindisfarne, Northumberland. 2. Fat and pectoral muscle as indicators of body condition in the Bar-tailed Godwit - Evans, P R; Smith, P C (Wildfowl, 1975)
Body compositions have been determined of 169 Bar-tailed Godwits Limosa lapponica, collected at different times of year, between 1970 and 1975, at Lindisfarne, Northumberland. Normal trends in lipid and muscle indices are shown in Figure 4. The lipid index (weight of fat as a percentage of total body weight) of both adults and juveniles reaches a peak in December when daylight hours are shortest. Both muscle indices (lean dry weight of all the pectoral muscles (i) as a percentage of lean body weight (ii) in relation to skeletal size) remain unchanged in adults throughout the non-breeding season, but increase steadily in juveniles to reach adult levels by late winter. Slight hypertrophy of the pectoral muscles may occur before migration. Birds with lipid and/or muscle indices below normal for the time of year are considered to be in 'poor condition'; recovery of condition may be rapid, for example in adult godwits arriving at Lindisfarne with depleted muscles after autumn migration. During cold weather, lipid reserves are used to augment daily food intake if this is insufficient to meet daily energy requirements. At maximum, fat reserves alone could supply about three days' energy needs. Muscle may also be drawn upon as a protein reserve. Juveniles lose condition more rapidly than adults when food becomes less readily available in cold weather. Differences in the temporal pattern and functions of winter fattening in waders and passerines are discussed. Some predictions are made as to the likelihood of accumulation of protein reserves in winter or before migration in different bird species.